From Words to Meaning: Examining the Translation Process - Valerina Prasetya; Mohammad Nu'man; Muhammad Azwar; Muhammad Amien Rais (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
Translation is the process of transferring meaning from a source language to a target language while preserving the message, context, and communicative intent of the original text. In the context of Arabic, translation poses unique challenges due to its rich morphological structure, flexible syntax, and context-dependent semantic nuances. This study aims to examine the translation process and several translation models developed by leading scholars. The method used is library research by collecting and analyzing literature related to translation theory and practice. The findings show that the translation process involves analysis, transfer, and restructuring stages, although each expert emphasizes different approaches. The classical model focuses on lexical equivalence, Nida and Taber highlight dynamic equivalence, Suryawinata emphasizes deep and surface structure, while Newmark focuses on contextual and stylistic interpretation. Understanding these models enables translators to produce more accurate, natural, and contextually appropriate translations.